Interferon-gamma ameliorates experimental autoimmune encephalomyelitis by inducing homeostatic adaptation of microglia - Tichauer, Juan; Arellano, Gabriel; Acuña, Eric; González, Luis F.; Kannaiyan, Nirmal R.; Murgas, Paola; Panadero-Medianero, Concepción; Ibañez-Vega, Jorge; Burgos, Paula I.; Loda, Eileah; Miller, Stephen D.; Rossner, Moritz J.; et al. (Frontiers in immunology, 2023)
Compelling evidence has shown that interferon (IFN)-γ has dual effects in multiple sclerosis and in its animal model of experimental autoimmune encephalomyelitis (EAE), with results supporting both a pathogenic and beneficial function. However, the mechanisms whereby IFN-γ may promote neuroprotection in EAE and its effects on central nervous system (CNS)-resident cells have remained an enigma for more than 30 years. In this study, the impact of IFN-γ at the peak of EAE, its effects on CNS infiltrating myeloid cells (MC) and microglia (MG), and the underlying cellular and molecular mechanisms were investigated. IFN-γ administration resulted in disease amelioration and attenuation of neuroinflammation associated with significantly lower frequencies of CNS CD11b+ myeloid cells and less infiltration of inflammatory cells and demyelination. A significant reduction in activated MG and enhanced resting MG was determined by flow cytometry and immunohistrochemistry. Primary MC/MG cultures obtained from the spinal cord of IFN-γ-treated EAE mice that were ex vivo re-stimulated with a low dose (1 ng/ml) of IFN-γ and neuroantigen, promoted a significantly higher induction of CD4+ regulatory T (Treg) cells associated with increased transforming growth factor (TGF)-β secretion. Additionally, IFN-γ-treated primary MC/MG cultures produced significantly lower nitrite in response to LPS challenge than control MC/MG. IFN-γ-treated EAE mice had a significantly higher frequency of CX3CR1high MC/MG and expressed lower levels of program death ligand 1 (PD-L1) than PBS-treated mice. Most CX3CR1highPD-L1lowCD11b+Ly6G- cells expressed MG markers (Tmem119, Sall2, and P2ry12), indicating that they represented an enriched MG subset (CX3CR1highPD-L1low MG). Amelioration of clinical symptoms and induction of CX3CR1highPD-L1low MG by IFN-γ were dependent on STAT-1. RNA-seq analyses revealed that in vivo treatment with IFN-γ promoted the induction of homeostatic CX3CR1highPD-L1low MG, upregulating the expression of genes associated with tolerogenic and anti-inflammatory roles and down-regulating pro-inflammatory genes. These analyses highlight the master role that IFN-γ plays in regulating microglial activity and provide new insights into the cellular and molecular mechanisms involved in the therapeutic activity of IFN-γ in EAE.
Veröffentlicht: 02. Juni 2023
Gesehen am 14.08.2023